Sellar chondrosarcoma presenting with amenorrhea: A case report. Issue 27 (July 2018) - Cao, Junguo; Li, Guihong; Sun, Yuxue; Hong, Xinyu; Huang, Haiyan
Abstract: Rationale: Intracranial chondrosarcomas are rare entities and most of which arise off the midline. Chondrosarcomas that occur in the sellar region are extremely rare, and to the best of our knowledge, there is no reporting about sellar chondrosarcoma with amenorrhea as the onset symptom. Patient concerns: A 45-year-old woman presented with a 7-month history of amenorrhea and a 3-month history of progressive visual loss in the left eye. Diagnosis: The patient was diagnosed with recurrent sellar chondrosarcoma arising from intrasellar with extensive tumor invasion into bilateral sphenoid sinuses. Interventions: Twice endonasal transsphenoidal tumorectomies were performed followed with a stereotactic radiotherapy and hormone replacement therapy. Outcomes: The patient's condition was stable and her visual symptoms improved, the hormones returned to normal, and no recurrence was noted on MRI after six months. Lessons: Sellar chondrosarcomas with the onset of endocrine dysfunctions are extremely rare, which may be misdiagnosed as pituitary adenoma and the definitive diagnosis depends on histopathological and immunohistochemical evidence. The first choice of treatment is surgery with the goal of complete resection, and postoperative adjuvant radiotherapy should be highlighted.